Analisis Co-Firing Kulit Kayu terhadap Emisi dan SFC PLTU Balikpapan - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Wenny Retno Astagina (JTM : JURNAL TEKNIK MESIN, 2026)
Co-firing is a practical approach to reduce coal dependency and improve environmental performance in existing coal-fired power plants. This paper evaluates 3% wood bark co-firing at Unit 2 of PLTU Teluk Balikpapan 2 x 110 MW, focusing on emissions, specific fuel consumption (SFC), and key operating parameters. The study compares baseline operation using 100% coal with operation using 97% coal and 3% wood bark. Fuel characteristics, boiler operating data, bottom ash observation, stack visual inspection, SFC calculation, and flue gas emission measurements are evaluated. Wood bark has lower sulfur content than coal, namely 0.13% compared with 0.59%, although its gross calorific value is lower. The co-firing test decreased SO2 emission from 246.7 mg/Nm3 to 190 mg/Nm3, equivalent to a reduction of 22.98%, while NOx increased from 285 mg/Nm3 to 307 mg/Nm3 but remained below the 550 mg/Nm3 emission limit. SFC changed slightly from 0.706 kg/kWh to 0.707 kg/kWh. Bed temperature decreased from 927.16 degC to 924.18 degC and FEGT decreased from 1013.78 degC to 1011.24 degC, indicating stable boiler operation. The test did not show black smoke, carry over, or significant agglomeration tendency. Therefore, 3% wood bark co-firing is technically feasible for emission reduction with limited impact on SFC.